Aktualisasi Falsafah Ekonomi Islam Sebagai Soko Dalam Membangun Kesejahteraan - Suaidi Suaidi (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
Islamic economic theory is not a new theory that is derived to underlie the existing economy. Historically, Islamic thinkers are the founders of all branches of knowledge, including economics. This is recognized by Islamic economists that since 367-322 BC they read a lot of Aristotle's works as a philosopher who wrote a lot about economics, but Islamic economists think about economics based on the Al-Quran and al-Hadith. This study aims to explore the basic thoughts and reflections on the philosophy of Islamic economics which is oriented towards raising the welfare of mankind which avoids usury practices that are contrary to the mission of the Koran and al-Hadith concerning the economy, as a basis for bringing up human welfare that is clean from usury practices.